2009
DOI: 10.5194/cp-5-667-2009
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope records for the last 10 000 years from Okshola cave (Fauske, northern Norway) and regional comparisons

Abstract: Abstract. The sensitivity of terrestrial environments to past changes in heat transport is expected to be manifested in Holocene climate proxy records on millennial to seasonal timescales. Stalagmite formation in the Okshola cave near Fauske (northern Norway) began at about 10.4 ka, soon after the valley was deglaciated. Past monitoring of the cave and surface has revealed stable modern conditions with uniform drip rates, relative humidity and temperature. Stable isotope records from two stalagmites provide ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…The majority of the records highlight a transition between warmer and colder periods around the 14th century. Two records are characterized by an ending point after the 15th century (Arc_49, Linge et al, 2009;Arc_38, Berner et al, 2011). The time coverage of the MCA is about ∼ 200-250 years in most records (Fig.…”
Section: Secular Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the records highlight a transition between warmer and colder periods around the 14th century. Two records are characterized by an ending point after the 15th century (Arc_49, Linge et al, 2009;Arc_38, Berner et al, 2011). The time coverage of the MCA is about ∼ 200-250 years in most records (Fig.…”
Section: Secular Variabilitymentioning
confidence: 99%
“…ported to be as late as AD 1900 (e.g., Gunnarson et al, 2011;Isaksson et al, 2005;Linge et al, 2009;Massa et al, 2012) (Fig. 7a and b).…”
Section: Secular Variabilitymentioning
confidence: 99%
“…yr BP, that are characterized by high Ti and low TOC values indicative of high (summer) precipitation and/or snow melt, correspond to periods with low δ 18 O in a speleothem (SG 93) from Soylegrotta (66°N13°E), Rana, Norway (Lauritzen and Lundberg, 1999). Low δ 18 O at this cave site is thought to represent warm and wet climate conditions (Linge et al, 2009;Sundqvist et al, 2010). The similarity between the Vuoksjávrátje Ti and SG 93 δ 18 O suggests a common response to changes in precipitation patterns, most likely due to shifts in the atmospheric circulation.…”
Section: Comparison With Other Palaeoclimate Recordsmentioning
confidence: 84%
“…Presence/absence of growth and growth rate can thus both be powerful proxies for palaeoclimate conditions (e.g., [134,151,152]), with growth cessation and/or slow growth rates indicative of drier/colder stages, such as glacials and stadials ( Figure 3A). This is observed at the Scandinavian cave sites, where speleothem growth is limited to interglacial time periods [47,107]. Conversely, evidence from high Alpine caves has shown that "subglacial" speleothem growth is possible if carbonate dissolution is promoted by sulphide oxidation, for instance seen in stalagmites from Milchbach and Sieben Hengste Caves, Switzerland [104,114] and Spannagel Cave, Austria [119].…”
Section: Climate Controls On Speleothem Growthmentioning
confidence: 99%